TENAGA KERJA INDONESIA (TKI) DAN HUBUNGAN INDONESIA-MALAYSIA ERA JOKOWI - Ali Maksum (Jurnal PIR : Power in International Relations, 2018)
Following the leadership succession in the post Presidential Election in 2014 from the 6th Indonesian President Susilo Bambang Yudhoyono to the 7th Indonesian President Joko Widodo (Jokowi), the Indonesian migrant workers became one of the priorities of the new government. The reason is simple, there are still many Indonesian workers especially in Malaysia who are involved in various problems and cases. The issue of protection of Indonesian citizens abroad became the primary agenda of Jokowi’s administration including protection on migrant workers. To be sure, the various issues of migrant workers eventually impact on the relationship between the two brotherhod countries, Indonesia and Malaysia. On the other hand, both countries were obviously gained so many advantages from the influx of Indonesian migrant workers in Malaysia. For Indonesian government for instance, the migrant workers is one of the largest revenue contributors from their remittance. As for Malaysia, the presence of Indonesian migrant workers were highly contributed to the national economy amid of the local people are lack of interested to such kind of dirty jobs. Therefore, this article would like to invite readers into a deep discussion comprehensively on the issues of migrant workers and their implications on the Indonesia-Malaysia relations especially in the first half of Jokowi’s tenure of presidency.